O08.6 Do You Have an STI? Findings from a Dedicated Men's Sexual Health Clinic in Alexandra Township, South Africa. (13th July 2013) - Lewis, D A; Ricketts, C; Vezi, A; Maseko, V
Abstract : Background: A walk-in weekly men's sexual health clinical service, provided by a male clinical team, was established in 2006. Methods: We analysed new patient episodes at a dedicated men's sexual health clinic in Alexandra Township, South Africa over 6 years (2007–2012). STI syndromes were treated immediately and all men were offered urine-based molecular screening for Neisseria gonorrhoeae (NG), Chlamydia trachomatis (CT), Trichomonas vaginalis (TV) and Mycoplasma genitalium (MG) infections and serological screening for syphilis. Clinical and laboratory data were analysed using STATA TM version 10. Results: Among the 876 new clinical episodes, the most common presentations were genital warts (432, 49.5%), male urethritis syndrome (188, 21.6%) and genital ulceration (82, 9.4%). The proportion of patients attending for genital wart treatment increased over time. Few men (51, 5.9%) presented as sexual contacts. The patients' peak age range was 25–29 years; only 40 (4.6%) men were < 20 years old. HIV testing history was provided by 871 men: 156/430 (36.3%) men who knew their serostatus were HIV positive but 441 (50.6%) had never tested. Laboratory testing of 822 urine specimens detected 108 (13.1%) NG, 100 (12.2%) CT, 51 (6.2%) TV and 68 (8.3%) MG infections. The syndromic approach alone would not have treated 16 (14.8%) NG, 57 (57.0%) CT, 46 (90.2%) TV and 49 (72.1%) MG infections. NG/CT infections were most prevalent among those aged 18–19 years old (34.5% and 17.2%, respectively); in contrast, TV/MG infections were most prevalent in the 35–39 year old age group (1.7% and 11.8%, respectively). The prevalence of rapid plasma reagin seroreactivity was 2.2%. Overall condom use was 16.9% with regular partners and 52.5% with non-regular partners. Conclusion: Asymptomatic STIs, poor clinic attendance by youth, poor uptake of HIV testing by men and low rates of condom use with partners remain challenges for STI management in South Africa.